Implementasi model pembelajaran creative entrepreneurship learning based discovery skills untuk meningkatkan keterampilan berpikir kreatif pada pembelajaran ipa materi energi peserta didik kelas iv sd - Pratama, Riky Rivaldi; Atmojo, Idam Ragil Widianto; Surya, Anesa (Universitas Sebelas Maret, 2019)
Creative thinking skills are essential skills for 21st-century life. Creative thinking skills are closely related to the ability to produce creative ideas to compete globally. The purpose of this research was to improve creative thinking skills using the Creative Entrepreneurship Learning Model-Based Discovery Skills (CEL-BaDiS). This type of research is classroom action research with the implementation of three cycles and each cycle consists of two meetings. Each consist of four steps there were planning, action, observation and reflection cycles. The data was collected by using several techniques such as observation, interview, documentation and creative thinking test. The interactive model was used to analyze the data. The assessment of research showed that both students' creative thinking and teacher's performance increased continuously. Based on the results, it can be concluded that trough double lo-problem solving models based on experiment enhancing the student's creative thinking skills of heat and transfer for grade IV students.